Study on the performance of a centrifugal compressor considering running tip clearance. (May 2016) - Kim, Changhee; Lee, Horim; Yang, Jangsik; Son, Changmin; Hwang, Yoonjei
Highlights: The effect of impeller deformation on flow field and performance is investigated. Running tip clearance is predicted using fluid–structure interaction method. The uniform tip clearance changed to non-uniform due to impeller deformation. Performance increases due to reduction in the tip clearance. Abstract: A series of aero-thermo-mechanical analyses were carried out to predict the running tip clearance and the effects of impeller deformation on the performance using two different centrifugal compressors (blade type A and B). In operation, impeller deformation due to the combination of centrifugal force, aerodynamic pressure and thermal load results in non-uniform tip clearance profile. The results show that the maximum displacement occurs at the leading edge tip of the impeller blade but maximum stress takes place at the blade root of the impeller. A significant reduction of the tip clearance height has occurred at the leading edge and the trailing edge of the impeller. Due to the reduction of the tip clearance, the tip leakage flow has decreased by 19.4% and 16.2% in the blade type A and B, respectively. The polytropic efficiency of blade type A and B at operating condition has increased by 0.72% and 1.81%, respectively.